Nest-site selection, territory quality and breeding performance in a Blue Tit Cyanistes caeruleus population (Acta Oecologica, 2012)
Patterns of territory selection and sources of variation for reproductive performance in a Blue Tit Cyanistes caeruleus population breeding in nest-boxes during years 2007 and 2008 in a holm oak forest are analyzed. Territory selection has been assessed as a function of two ﬁxed effect factors: territory location (peripheral vs. interior in the nestbox patch) and nestbox type (entrance hole: 26 mm vs. 32 mm). Breeding density was independent of these factors. Pairs nesting in periphery nest-boxes and in smallholed nestboxes owned territories bigger than those nesting in interior and large-holed nestboxes, respectively. The breeding traits studied were laying date, clutch size, hatching success, ﬂedgling success and breeding success. Egg laying was earlier in periphery territories and small-holed nestboxes. Between-year variation was a factor signiﬁcantly affecting to all breeding traits. Clutch size declines in late clutches. Hatching success was higher in territories with more tree density. Although egg laying started earlier in some territories, the mean breeding success was similar in all of them. However, territories with the greatest contribution of individuals to the population were those with small-holed nestboxes. Breeding success in successful pairs had a tendency to be higher in pairs with late clutches and in those nesting in interior territories with large-holed nestboxes. Both decreased breeding success and total breeding failure were much more important in the second breeding year than in the ﬁrst one. The high breeding density of Blue Tit, favored by the experimental design of nestbox plot, did not suggest signiﬁcant variation between territories in terms of breeding success achieved. Implications for nestbox management are discussed.